Family Educational Style and its Relationship to Aggressive Behavior among High School Students )It is a Field Research in Ranya( - Omer Mahmood, Dastan; Ismail Bakr, Juan (Zanco Journal of Human Sciences, 2023)
Family educational practices are one of the issues whose effects and consequences are not immediately apparent. That is, the parental educational style may not have an immediate effect on the child, but it may have effects and consequences during adolescence or youth. Consequently, family educational patterns directly and indirectly determine individual behavior patterns, including aggressive behaviors. The main objective of the study is to find the relationship between family parenting styles with aggressive behavior patterns. The researcher also used the descriptive analytical method to analyze the objectives. For this purpose, he prepared a form that consisted of 38 items for family education and 26 items for aggressive behavior. Meanwhile, a random sample of 400 high school students in Ranya, including) 212( males and )188( females, was selected. The researcher used both SPSS and AMOS statistical programs. The most significant findings of this study are that females are more likely to be treated with "democratic and overprotective - pampering" education methods, while males are more likely to be treated with "coercive, discriminatory, neglectful, corporal punishment" methods. Aggressive behavior “physical and verbal” was also more common in males than females. However, this distinction does not exist with regard to aggressive behavior. Each of these methods (coercive and discriminatory) has directly led to self-aggressive behavior. While the method of education (corporal punishment) directly led to the emergence of verbal aggressive behavior. The gender variable has changed the "relationship of the independent variable to the suffix" In a sense; the (coercive) educational style has led to the emergence of verbal aggressive behavior in males, but not in females. Methods (discrimination, physical and punishment) also led to physical aggressive behavior in males, but not in females.